Empowering Lay Rescuers in Out-of-Hospital Cardiac Arrest: A Pretest-Posttest Study Guided by Orem’s Self-Care Deficit and Neuman’s Systems Models - Irni Fuzi Wijayanti; Fitriana Kurniasari Solikhah (Tarqabin Nusantara Group, 2026)
Introduction: Out-of-hospital cardiac arrest (OHCA) has a low survival rate, making bystander Basic Life Support (BLS) crucial. However, in Indonesia, bystander intervention is frequently hindered by knowledge deficits, cultural norms regarding cross-gender touch, and fear of legal liability. This community service aimed to enhance the BLS competence of PIA Ardhya Garini members as first responders, theoretically grounded in Orem’s Self-Care Deficit and Neuman’s Systems Models. Methods: A quasi-experimental one-group pretest-posttest design was employed involving 60 PIA members. The intervention was a contextualized BLS training integrating legal empowerment (Indonesian Good Samaritan Law), cultural adaptation, and demographic adjustments (Hands-Only CPR for middle-aged women). Effectiveness was evaluated using a validated 10-item cognitive test, and data were analyzed using the Wilcoxon signed-rank test and Normalized Gain (N-Gain). Results: The intervention significantly improved participants' cognitive knowledge. The mean score increased from 6.87 ± 0.96 (pretest) to 9.03 ± 0.74 (posttest) with a p-value < 0.001. The Normalized Gain (N-Gain) was 0.67, indicating moderate effectiveness. The training successfully corrected clinical misconceptions and mitigated specific socio-cultural and legal barriers to bystander intervention. Conclusion: Integrating nursing theories with socio-cultural-legal-clinical modifications effectively empowers laywomen as